Extracellular vesicles: fundamentals and clinical relevance - Wael Nassar; Mervat El-Ansary; Mostafa Abdel Aziz; Ehab El-Hakim (SpringerOpen, 2015)
All types of cells of eukaryotic organisms produce and release small nanovesicles into their extracellular environment. Early studies have described these vesicles as 'garbage bags' only to remove obsolete cellular molecules. Valadi and colleagues, in 2007, were the first to discover the capability of circulating extracellular vesicles (EVs) to horizontally transfer functioning gene information between cells. These extracellular vesicles express components responsible for angiogenesis promotion, stromal remodeling, chemoresistance, genetic exchange, and signaling pathway activation through growth factor/receptor transfer. EVs represent an important mode of intercellular communication by serving as vehicles for transfer between cells of membrane and cytosolic proteins, lipids, signaling proteins, and RNAs. They contribute to physiology and pathology, and they have a myriad of potential clinical applications in health and disease. Moreover, vesicles can pass the blood-brain barrier and may perhaps even be considered as naturally occurring liposomes. These cell-derived EVs not only represent a central mediator of the disease microenvironment, but their presence in the peripheral circulation may serve as a surrogate for disease biopsies, enabling real-time diagnosis and disease monitoring. In this review, we'll be addressing the characteristics of different types of extracellular EVs, as well as their clinical relevance and potential as diagnostic markers, and also define therapeutic options.